Glossoscolex (Glossoscolex) canchim sp. nov. and Fimoscolex bernardii sp. nov., two new earthworm species (Oligochaeta: Glossoscolecidae) from São Paulo State, Brazil - Bartz, Marie Luise Carolina; Bruz, Liliane Dos Santos Maia; Brown, George Gardner (Zootaxa, 2026)
Brazil harbors one of the richest earthworm faunas worldwide, yet a substantial portion of its diversity remains undescribed. In this study, two new species of Glossoscolecidae are described from the Canchim Farm, São Carlos, São Paulo State, Brazil. The species were collected in experimental areas of integrated forest-crop-livestock systems (agrosilvopastoral systems), and in annual crops under no-tillage management. One species belongs to the genus Fimoscolex and the other to the subgenus Glossoscolex in the genus Glossoscolex. Fimoscolex bernardii sp. nov. is characterized by a single male pore in segment XVII associated with a copulatory chamber and by the presence of a ventral ovisac extending from segment XII to XIV, a structure interpreted as part of the female reproductive apparatus. Glossoscolex (Glossoscolex) canchim sp. nov. exhibits the diagnostic characters of the Glossoscolex (Glossoscolex) truncatus group, including paired male pores in segment XVII associated with paired copulatory chambers, and differs from congeners mainly in size and shape of the calciferous glands and copulatory chambers and clitellar morphology. Comparative morphological data with closely related species are provided. The occurrence of these new species in managed agricultural systems highlights the relevance of sustainable land-use practices for the persistence of native soil fauna and reinforces the need for continued taxonomic and ecological studies of earthworms in southeastern Brazil.